Remote consultations in prison mental healthcare in England: impacts of COVID-19. Issue 2 (8th February 2021) - Hewson, Thomas; Robinson, Louise; Khalifa, Najat; Hard, Jake; Shaw, Jennifer
Summary: Telemedicine has become increasingly used by prison mental health services throughout the COVID-19 pandemic. In this editorial, we explore the benefits and risks of the remote provision of forensic mental healthcare, with consideration of the clinical, financial, ethical and legal consequences.